2010
DOI: 10.1002/aqc.1120
|View full text |Cite
|
Sign up to set email alerts
|

Effect of type of bait on pelagic longline fishery–loggerhead turtle interactions in the Gulf of Gabes (Tunisia)

Abstract: ABSTRACT1. Sea turtles may migrate vast distances from their feeding areas to home rookeries where they nest. During these migrations sea turtles are subject to many threats, among which are interactions with pelagic longlines.2. This gear is used frequently in the summer period in the Gulf of Gabes targeting mainly the sandbar shark (Carcharhinus plumbeus). Hooks are baited with mackerel (Scomber scombrus) or pieces of stingray (Dasyatis pastinaca).3. Twenty-one fishing trips (48 sets with a total of 35 950 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 19 publications
4
25
2
Order By: Relevance
“…How this behaviour under laboratory conditions relates to behaviour in the wild during an incidental capture is not known. However, our findings support field observations that the type of bait can influence the loggerhead bycatch rate (Echwikhi et al 2010) and higher loggerhead bycatch rates occur when using pelagic longline gear deploying squid baits compared to gear using mackerel baits (Báez et al 2010).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…How this behaviour under laboratory conditions relates to behaviour in the wild during an incidental capture is not known. However, our findings support field observations that the type of bait can influence the loggerhead bycatch rate (Echwikhi et al 2010) and higher loggerhead bycatch rates occur when using pelagic longline gear deploying squid baits compared to gear using mackerel baits (Báez et al 2010).…”
Section: Discussionsupporting
confidence: 85%
“…Different types of baits have been tested at sea to verify their effectiveness in mitigating turtle bycatch without affecting the catch of target species (Echwikhi et al 2010 developed and to that end further investigation of the relationships between chemical cues and prey appearance could be of value.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Mejuto et al (2008) observed higher catch rates of loggerhead and olive ridley sea turtles on pieces of blue shark for bait than with squid or mackerel for bait. Echwikhi et al (2010) observed significantly lower loggerhead turtle catch rates with pieces of stingray used for bait versus whole mackerel.…”
Section: Bait Typementioning
confidence: 86%
“…The FAO guidelines require longline fisheries to develop and implement modifications in hook design, bait species, depth, gear specifications and fishing practices in order to minimize sea turtle incidental bycatch and mortality (FAO, 2005). Recently, trials using different types of bait have been used as a mitigation method to reduce sea turtle bycatch in longline fisheries (Swimmer et al, 2005;Watson et al, 2005;Yokota et al, 2009;Echwikhi et al, 2010).…”
Section: Pelagic Longline -Sea Turtle Interactionsmentioning
confidence: 99%
“…In fact, evaluation of the potential impacts of bait modifications on the catch efficiency for target and non-target species is necessary (Swimmer et al, 2005;Gilman et al, 2006b;Yokota et al, 2009;Echwikhi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%